Specifications of a device interface for service-oriented automation control components - Barbosa, José (2010)
Service-oriented paradigm is being used to develop distributed and reconfigurable control solutions for factory automation environments. Since service-oriented automation control components are logical entities that provide and consume services, they may have an interface that maps the logical processes into the actions of the representative physical mechatronics. The inter-connection with the physical hardware devices, namely accessing I/Os, is a crucial issue to achieve the vertical IT-enterprise integration in these service-oriented systems, covering the shop floor device control level. This paper describes a device interface approach, in the context of a service-oriented control architecture, in which High-level Petri nets are used as the control description to access to the physical device. The outgoing features of the solution allow integrating the physical behavior into the control of automation components and consequently thereby incorporate it in the modular service-oriented control architecture.